Media Roles in Islamic Conversion: A Study in Sabah, Sarawak and Brunei - Salinayanti, Salim (2018)
This paper examines the roles of media in the conversion of the Muslim converts in Sabah, Sarawak andBrunei. The media involved are traditional media and social media. The data was collectedthrough one-on-oneinterviewswith the Muslim converts who resided in Sabah, Sarawak andBrunei. The data was then analysed using descriptive andinterpretive approaches. The findingswere categorisedinto two major themeswhich represented the overall responses of the informants towards the roles of media in Islamic conversion,the media roles in the time of conversion,and the types of media used in the conversion. The findingsreveal that the media played roles in the conversions of all the informants in the study. The roles of media and their uses in the time of conversion are quite similar in the Sabah and Sarawak findings, whereas there is a significant difference in the Brunei finding. As for the types of media, traditional media have more importantroles in Islamic conversion in Sabah, Sarawak andBrunei.